Sexual Dysfunction in Chronically Medicated Male Inpatients With Schizophrenia: Prevalence, Risk Factors, Clinical Manifestations, and Response to Sexual Arousal - Liu, Dianying; Liu, Shaohua; Xiu, Meihong; Deng, Hongdong; Guo, Huiyun; Liu, Wanglin; Zhang, Delong; Mao, Zhongzhen; Huang, Dan; Huang, Donghua; Miao, Qiumei; Qiu, Lijuan; et al. (Frontiers in Psychiatry, 2022)
Background: Sexual dysfunction is a common symptom in patients with schizophrenia, especially in chronically medicated patients. However, the relationship between sexual dysfunction and emotional response to sexual arousal in male patients with schizophrenia remains unclear. This study aimed to assess the incidence, risk factors of sexual dysfunction in male, and their clinical correlations to sexual arousal in male patients with schizophrenia in China. Methods: A total of 162 male patients, aged 18 to 50 years old, with schizophrenia were recruited from a psychiatric hospital in Ganzhou. The clinical symptoms were assessed by the Positive and Negative Syndrome Scale (PANSS). The Arizona Sexual Experience Scale was utilized to evaluate sexual dysfunction. Erotic images were selected from International Affective Picture System (IAPS). Sixty eight out of the 162 subjects completed affective reactivity task. Results: Overall, 48 (29.6%) patients were measured having global sexual dysfunction, 72 (44.4%) patients having strength of sex drive dysfunction, 51 (31.5%) patients having sexual arousal dysfunction, 55 (34.0%) patients having penile erection dysfunction, 60 (37.0%) patients having reach orgasm dysfunction and 60 (37.0%) patients having satisfaction with orgasm dysfunction. The sexual dysfunction patients had significantly higher scores on the negative symptom of PANSS. The only important predictor of sexual dysfunction was the severity of PANSS negative factor. The sense of pleasure and arousal post viewing erotic images in the sexual dysfunction group were lower compared to the non-sexual dysfunction group. The sense of pleasure and approach motivation were significantly negative correlated with the severity of sexual dysfunction. Conclusions: This study shows that nearly 1/3 of young and middle-aged chronically medicated male inpatients with schizophrenia suffer from sexual dysfunction. The negative factor of the PANSS can be regarded as the risk factor of sexual dysfunction.Schizophrenia patients with sexual dysfunction experienced lower pleasure and higher avoidance motivation than non-sexual dysfunction patients when exposed to erotic stimulus.